Transformasi Akad: Peran Platform E-Commerce dalam Menjembatani Perdebatan Shighat dan Mitigasi Gharar pada Jual Beli Kontemporer - Hakim, Luqman; Al Yamani, Jalaluddin; Salsabila, Tasya (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2025)
The digital revolution has fundamentally transformed commercial transactions, giving rise to practices such as pre-orders in e-commerce. This study examines how contemporary e-commerce platforms not only transform the classic Bai' as-Salam contract but also address the classical jurisprudence （fiqh debate regarding the validity of the contract form （shighat. Traditionally, schools of fiqh （such as Hanafi and Syafi'i） have differed on the validity of non-verbal contracts （mu'athah） due to potential uncertainty （gharar. This article argues that modern e-commerce platforms function as a "standardized digital shighat". Through features like detailed product descriptions, visualizations （photos/videos）, the 'checkout' button as ijab-qabul （offer and acceptance）, and review systems, these platforms create a form of mu'athah that is more certain and whose risks are mitigated. Using comparative legal analysis and literature review, this study analyzes how modern digital architecture manages gharar in pre-order practices. Findings indicate that digital platforms bridge the flexibility (e.g., the Hanafi school) with the demand for certainty (e.g., the Syafi'i school), thereby reinforcing the relevance of fiqh muamalah principles in the digital economy.